Quantitative techniques : an instructional manual - Lucey, T. (London : DP Publications, 1988)
This instructional manual is designed to provide a sound understanding of quantitative techniques and is particularly designed for professional examinations.
oif 28/01/2019
Loans
Keywords: Business mathematics; Accounting; Operations research; Management science; Quantitative techniques